Challenges in antenatal diagnosis of conjoined twins in primary care setting: a case report - Jamani, Nurjasmine Aida; Sururi, Nur Fitrahana; Husin, Roziah (Universiti Kuala Lumpur (UniKL), 2025)
Conjoined twins (CT) represent a rare embryologic anomaly with anuncertain aetiology. Although uncommon, this condition is associated with a high perinatal mortality rate. Early detection during the first trimester is therefore crucial to enable timely intervention and referral to a tertiary care centre. First-trimester dating scans in primary care areessential not only for confirming viability and determining gestational age but also for identifying multiple pregnancies. However, anomalies in twin pregnancies-such as conjoined twins-may be overlooked during these early scans due to various challenges. This case report discusses the difficulties in detecting CT and explores factors that may contribute to missed diagnoses.